THE IMPORTANCE OF THE FORMATION OF SOCIO-PERSONAL KOMPETENT I IN SCHOOLCHILDREN-YOUTH - Farhod Makhsiddinovich Norbo’tayev; Imomova L.Z. (Journals Park Publishing, 2022)
The role of a person in raising spirituality, the formation of a culture of reading among students and girls, the reading of a book leads a person to spiritual perfection, the formation of a person as a comprehensively mature, perfect person is incredibly incomparable. In particular, valuable information was given on such issues as human perfection, spiritual maturity, patriotism, education and training in the oral creativity of the people, views, ideas and works of Eastern thinkers.In this article, some facts about the role of scientists in the formation of students spirituality, upbringing in the spirit of loyalty to our national and universal values and their theoretical bases will be presented.
Keywords: spirituality; morality; education